Edukasi Perhitungan Harga Pokok Penjualan untuk Meningkatkan Penjualan pada Kube Wanita UMKM Pamulang Estate - Khuluqi, Khusnul; Sugeng, Andry; Soeparyono, Regina Deia (Perhimpunan Sarjana Ekonomi dan Bisnis, 2024)
Education regarding how to calculate COGS is very important so that MSMEs can maximize their business development potential. Errors in determining COGS can result in business losses. Therefore, education about COGS calculations is vital to help MSMEs achieve competitive advantage and maximize business development potential. MSMEs are independent productive economic enterprises, usually carried out by individuals or business entities that are not subsidiaries or branches of companies owned, controlled or part of directly or indirectly. The business actors in this activity are the Pamulang Estate UMKM Women's Kube. This Community Service activity aims to provide education regarding calculating the cost of goods sold to increase MSME sales. The method developed in this activity involves socializing the calculation of cost of goods sold to increase sales at the Pamulang Estate UMKM Women's Kube. The problem faced by MSME players is related to a lack of knowledge regarding calculating the cost of goods sold in their business so that MSMEs are inaccurate in determining the cost of goods sold and determine the selling price incorrectly. MSME players argue that they do not have knowledge regarding calculating the good and correct cost of goods sold. So that this activity regarding calculating the cost of goods sold can provide business actors with insight, knowledge and skills in understanding the correct calculation of the cost of goods sold and can directly apply it in their business.